MODEL PENTA HELIX DALAM PEMBERDAYAAN DESA DIGITAL DI KECAMATAN IBUN, KABUPATEN BANDUNG - Nunu Mahmud Firdaus; Ai Sarah Naudyah Cahyani (IKIP Siliwangi, 2023)
One of the government's efforts to empower the community during the Covid 19 pandemic is the penta helix collaboration in the digital village. The purpose of this research is to investigate the pentahelix collaboration model in empowering digital village communities in the Covid-19 pandemic situation. The theory used in this study is the theory of community empowerment, the theory of the era of digitalization of online marketing media, the theory of evaluative methodology in community empowerment and the penta helix theory as a supporter of community empowerment. This research uses a qualitative approach with a descriptive method. In this study the instruments used were observation, interviews and documentation. The main reason for using this instrument is to collect data regarding the extent of the Penta Helix collaboration in empowering people in digital villages and draw conclusions about this by interpreting the data. The research population is all elements in Ibun District, Bandung Regency and the samples are two village heads, two heads of non-formal education institutions, five members of the community and two MSMEs managers who are currently in the process of developing digitalization. The results of the study show that there is synergy carried out by stakeholders such as the government, private sector, institutions and communities in the development of digital villages in the era of globalization. The conclusion of this study is that the penta helix model that is applied in the Ibun sub-district collaborates well, this can be seen in the development of the ability of village communities to carry out digital activities.